Numerical Simulation Of A Microchannel For Microelectronic Cooling - Wong, Wai Hing; Mohd. Ghazali, Normah (Penerbit UTM Press, 2007)
The paper discusses the numerical simulation of a micro-channel heat sink in microelectronics cooling. A three-dimensional Computational Fluid Dynamics (CFD) model was built using the commercial package, FLUENT, to investigate the conjugate fluid flow and heat transfer phenomena in a silicon-based rectangular microchannel heatsink. The model was validated with past experimental and numerical work for Reynolds numbers less than 400 based on a hydraulic diameter of 86 mm. The investigation was conducted with consideration of temperaturedependent viscosity and developing flow, both hydrodynamically and thermally. The model provided detailed temperature and heat flux distributions in the microchannel heatsink. The results indicate a large temperature gradient in the solid region near the heat source. The highest heat flux is found at the side walls of the microchannel, followed by top wall and bottom wall due to the wall interaction effects. Silicon is proven to be a better microchannel heatsink material compared to copper and aluminum, indicated by a higher average heat transfer. A higher aspect ratio in a rectangular microchannel gives higher cooling capability due to high velocity gradient around the channel when channel width decreases. Optimum aspect ratio obtained is in the range of 3.7 - 4.1.